Optimal source substation location selection in radial distribution networks - Islam, Shah Jahirul; Mustafa, Mohd. Wazir; Ismail, Hasan (2004)
New computer algorithm has been developed to select the optimal location of source substation in radial distribution networks. Selection methodology has been developed based on the geo-graphical location of connected substation of source substation, user's defined obstacle area by determining minimal route of the networks based on minimal loss of the networks and economic consideration. For the best location selection of source substation two steps selection method has been implemented for minimizing computer computation time. In the first steps it determines the projected area for the selection of optimal location of source substation. In the seconds step precise calculation is involved. Depending on the precise calculation of area selection computation time will be varied. Simulated example has been introduced for detail explanation of the output of computer algorithms.